Mahbub Djunaidi, Seniman Politik Nahdlatul Ulama (1960-1987) - Farhan Nugraha; Muhammad Fakhruddin; Humaidi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2021)
Nahdlatul Ulama is one of the largest Islamic organizations in Indonesia. This organization was born of course from the big figures who oversee it, one of them Mahbud Djunaidi. His political abilities are obtained from various organizational experiences and abilities in writing. The problem raised in this research is how the political history of Mahbub Djunaidi as a political activist of Nahdlatul Ulama in 1960-1987. Based on these problems, this study aims to describe the political journey of Mahbub Djunaidi (1960-1987). Based on the problems and objectives of the research, the method used is the historical method which consists of heuristics, source criticism, interpretation and historiography stages. The results of the study show that Mahbub Djunaidi has the concept of khittah plus. Political democracy in the style of Mahbub Djunaidi is the ideal of democracy which is fought for through political lines.